Pembuatan Direktori Objek Wisata Kabupaten Solok Provinsi Sumatera Barat - Sari, Tri Kurnia; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The aims of this research are (1) making Solok tourist object directory in West Sumatera amounted to 203 tourist objects and that author can get about 21 tourist objects consisting of some districtsthat located in Solok, this matter is caused by the limited time, a long distant location and cost a lot of money, (2) the way in generating the directory is collecting data, record data, focus on ideas, create a book framework, determine subject, classification or grouping and directory preparation, (3) the constraints in making location plan. The efforts of writing to overcome obstacles in making directories is making the best possible location plan so that the users ofinformation are simplified to find the tourist object they want to visit.Keywords: Tourist object, directory